Thrombopoietin receptor agonists in the treatment of chronic immune thrombocytopenic purpura (Hematology Meeting Reports, 2009)
Understanding of the pathophysiology of immune thrombocytopenic purpura (ITP) has undergone substantial revision. Harrington and colleagues showed that infusing ITP plasma into healthy recipients caused acute thrombocytopenia. Subsequently, this activity was attributable to the IgG fraction with the effect mitigated by splenectomy or corticosteroids. Formal studies of platelet kinetics affirmed that platelet survival is shortened in ITP. It was inferred from these studies, the abundance of megakaryocytes in the bone marrow and the appearance of young megathrombocytes in the periphery, that increased platelet production compensates for platelet destruction, analogous to reticulocytosis in autoimmune hemolytic anemia. Corticosteroids, danazol, IV immune globulin or IV anti-D worked by reducing clearance of antibody-coated platelets by tissue macrophages.